Strategic Nuclear and Non-Nuclear Deterrence in Russia’s National Security Policy - A. A. Kokoshin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
In the present context of a sharp aggravation of interstate rivalry and escalation of traditional and new threats, the importance of policy, forces and means of strategic deterrence in ensuring Russia’s national security cannot be overstated. Fundamental decisions on the development of strategic deterrence capabilities were made by the Russian leadership back in the late 1990s. These decisions were based on the long-term political and military forecasts first made by the Ministry of Defense and the Defense Council and then furthered by the Security Council of the Russian Federation. This paper examines how these decisions were put into practice in the subsequent years and how they have permeated the concept of strategic deterrence in Russia’s updated national security policy. The first section of the article identifies the key forces and facilities underlying the policy of the Russian Federation in the field of strategic nuclear deterrence. The author emphasizes that this policy is defensive in its nature and in terms of material capacities is based on achievements of Russian science and industry in general and the defense industry in particular. These advancements, in turn, rely on the foundations laid down in the USSR, and at the same time result from the timely modernization of Russia’s nuclear triad. The second section analyzes the role of non-nuclear deterrence in the national security policy of Russia. The author notes that a formidable threat of using a high-precision long-range conventionally-armed carrier within the framework of non-nuclear (‘pre-nuclear’) deterrence can effectively complement the nuclear deterrence system. That said, the author concludes that the solution to the problem of ensuring both nuclear and non-nuclear deterrence requires working out a large number of different scenarios, not only political ones, but also of a purely military, strategic and even tactical nature. It also necessitates the coordinated and systematic work of both military and civilian specialists representing the widest range of applied and fundamental disciplines.